Malnutrition risk and perception on dietary practices among elderly living in agricultural settlements: A mixed-methods research - Zainudin, Norain; Hamirudin, Aliza Haslinda; A. Rahman, Nor Azlina; Sidek, Suriati (Emerald Publishing Limited, 2019)
Purpose – This research aims to identify malnutrition risk and perception of malnourished and at-risk elderly individuals on their dietary practices. Design/methodology/approach – In Phase 1, a cross-sectional study was conducted among 413 elderly individuals aged 60 years and above in agricultural settlements in Kuantan, Pahang, Malaysia. Malnutrition risk was assessed using the Mini Nutritional Assessment Short-Form (MNA-SF). In Phase 2, in-depth semi-structured interviews were conducted among 21 elderly individuals identified in Phase 1. The interviews ceased when data saturation was achieved. Findings – 25.7 per cent (n = 106) of elderly individuals were identified as malnourished and at-risk (MNA-SF score = <12). Age, smoking, income and living status were significantly associated with malnutrition risk (p < 0.05). Thematic analysis revealed four themes that represent elderly individuals’ perception on their dietary practices: the impact of aging on dietary intake; food restriction according to health condition; poor dietary intake due to feeling of loneliness; and perceived benefits of foods for health. Research limitations/implications – Strategies from multidisciplinary healthcare professionals to eliminate improper dietary practice are required for the maintenance of health, functional independence and quality of life among the elderly. Originality/value – This research is at the forefront in reporting the elderly individuals’ perception on dietary practice in agricultural settlement. Attention to individual’s health issues and the associated factors that may influence their dietary practices is essential to provide appropriate interventions to achieve optimum nutritional status and healthy aging.